The Evaluation of the Usability in Mobile Applications - Adel ALZAHRANI; Valerie GAY; Ryan ALTURKI (Communications of International Proceedings, 2022)
With more people using smartphones in their everyday lives, it is more important than ever to make sure applications are intuitive. The importance of smartphones and the applications we use on them is rising rapidly. Everything from paying bills and getting in contact with loved ones to planning vacations and researching dining options is made easier with the help of these devices. The more we rely on our phones, the more it matters that they are simple to use. One of the most crucial factors in determining a program's success is the usability with which its target audience can utilize the program. There has been a lot of study on the usability of mobile apps over the past several years, but no one has yet worked out how to evaluate them fairly. This study reviews the existing literature on mobile app usability evaluation and gives some useful recommendations. We investigate the primary factors that are often considered when assessing the usability and highlight several other approaches that have been proposed for doing so in the context of mobile apps. Also, highlight some of the challenges associated with mobile app usability assessment and identify several potential future research directions for this area. There are a wide variety of approaches that may be used to assess the usability of a mobile app. By analyzing the findings of previous studies, we can create a set of criteria for judging the usefulness of existing products. The conclusion of the study discusses the study's summary and future goals.
Keywords: usability; mobile application; evaluation; attributes